Implementation of Restorative Justice at the Payakumbuh District Attorney's Office in the Case of Traffic Accident Crime Resulting in Minor Injuries - Ramadani, Sherly; Zulfiko, Riki (PAMALI: Pattimura Magister Law Review, 2025)
Introduction: The rapid development of transportation has revolutionized people's lives. Behind this progress there are challenges, namely the risk of traffic accidents. In everyday life, accidents that result in minor injuries can often be resolved with a more familial approach. The Payakumbuh District Attorney's Office, in an effort to realize harmonious justice, applies the concept of Restorative Justice as an alternative solution to resolve cases.Purposes of the Research: Examining the regulations governing criminal acts of traffic accidents which result in minor injuries with restorative justice efforts and the implementation of Restorative Justice for criminal acts of traffic accidents at the Payakumbuh District Prosecutor's Office.Methods of the Research: The research method used in this research is the juridical-empirical method, legal research regarding the application or application of normative legal provisions directly to each specific legal event that occurs in society.Results Main Findings of the Research: The basic implementation of restorative justice provisions in the Indonesian Prosecutor's Office is contained in the Republic of Indonesia Prosecutor's Regulation Number 15 of 2020. It is easy to carry out restorative justice efforts in this case because the victim is willing to forgive and reconcile with the suspect, the conditions for carrying out restorative justice efforts are fulfilled.